The role of organic rice farm income on farmer household welfare: Evidence from Yogyakarta, Indonesia - Triyono, Triyono; Al Qudsi, Muhammad Fahmi Faruqi; Nur Rahmawati; Rozaki, Zuhud; Kamarudin, Mohd Fauzi (Walter de Gruyter GmbH, 2024)
The study aims to know the farmer’s income from organic rice farming and farmer household income, to determine the welfare of farmer households. This research was conducted by data collection from 70 farmers’ households. The data analysis was used for the estimation of the farmer household income exchange rate and good service ratio. The results showed that the farmers are not yet prosperous. Further analysis to determine the role of organic rice farming for farming households has received less attention from researchers. Regarding this study, on-farm income derived from organic rice farming has a role as income contribution about 34.71% on the welfare of farmer households, classified as moderate.